Henry Kellett (1806-1875) - Neatby, L.H. (ARCTIC, 1987)
. Although he hardly rates as an explorer, Sir Henry Kellett rendered a most valuable service to polar history by rescuing the "Investigator" and so preserving the record of her sensational and often perilous voyage [through the Northwest Passage. Those seeking insight into the circumstances of the discovery of the Northwest Passage and the award of 10,000 Pounds Stirling to the officers and men of the Investigator, dismissing Kellett's rescue of McClure and his men, will especially appreciate this profile].